2009
DOI: 10.3109/17453670903350115
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of tumor necrosis factor activity promotes natural repair of osteochondral defects in rabbit knee

Abstract: Background and purpose Osteochondral defects have a limited capacity for repair. We therefore investigated the effects of tumor necrosis factor (TNF) signal blockade by etanercept (human recombinant soluble TNF receptor) on the repair of osteochondral defects in rabbit knees.Material and methods Osteochondral defects (5 mm in diameter) were created in the femoral patellar groove in rabbits. Soon after the procedure, a first subcutaneous injection of etanercept was performed. This single injection or, alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…37 An in vivo study showed that subcutaneous injection of etanercept promoted repair of osteochondral defects in the rabbit knee. 38 Application of the anti-TNFa monoclonal antibody in polyarthritic transgenic mice demonstrated reversal of cartilage degradation in the young mice. 39 Besides IL-1b and TNFa, proinflammatory cytokines, such as IL-6, 40 leukemia inhibitory factor, 41 and the chemokine IL-8, 42 may modulate the direct catabolic effects of some cytokines.…”
Section: Figmentioning
confidence: 99%
“…37 An in vivo study showed that subcutaneous injection of etanercept promoted repair of osteochondral defects in the rabbit knee. 38 Application of the anti-TNFa monoclonal antibody in polyarthritic transgenic mice demonstrated reversal of cartilage degradation in the young mice. 39 Besides IL-1b and TNFa, proinflammatory cytokines, such as IL-6, 40 leukemia inhibitory factor, 41 and the chemokine IL-8, 42 may modulate the direct catabolic effects of some cytokines.…”
Section: Figmentioning
confidence: 99%
“…When cartilage is damaged, high levels of extracellular mediators of inflammation including pro‐inflammatory cytokines and chemokines are produced by joint tissues and released in the synovial fluid . While low levels of these factors are required as initial stimulus for tissue repair, their increased or chronic production can impair chondrogenesis and stimulate the degeneration of newly‐formed cartilage . Among pro‐inflammatory mediators, IL‐1β, TNFα, members of the IL‐6 family, and IL‐8 are well recognized as potent anti‐chondrogenic factors .…”
Section: Extracellular Anti‐chondrogenic Regulatorsmentioning
confidence: 99%
“…Modulation of inflammation via targeted inhibition of pro‐inflammatory signals could offer great therapeutic benefits, by reducing cartilage degeneration and creating a favorable environment for repair. Kawaguchi et al showed that the repair of osteochondral defects in rabbit could be improved by injection of the TNF‐inhibitor etanercept. However, modulation of inflammation represents a considerable challenge since non‐selective inhibition of inflammation via non‐steroidal anti‐inflammatory drugs (NSAIDs) was found to inhibit chondrogenesis and cartilage production .…”
Section: Extracellular Anti‐chondrogenic Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many inflammatory cytokines, tumor necrosis factor-alpha (TNF-α) signaling and interleukin 1 beta (IL-1β) are the major mediators of cartilage destruction (Malemud, 2004). Inhibitors of secretion/activity of TNF-α and IL-1β including receptor agonists and monoclonal antibodies are capable of mitigating cartilage breakdown (Kawaguchi et al, 2009;Martel-Pelletier, Mineau, Jolicoeur, Cloutier, & Pelletier, 1998;Scott & Kingsley, 2006). Inhibitors of secretion/activity of TNF-α and IL-1β including receptor agonists and monoclonal antibodies are capable of mitigating cartilage breakdown (Kawaguchi et al, 2009;Martel-Pelletier, Mineau, Jolicoeur, Cloutier, & Pelletier, 1998;Scott & Kingsley, 2006).…”
Section: Introductionmentioning
confidence: 99%